Criminal Law Enforcement against the Abuse of Personal Data via the Internet in Indonesia - Mixon felly Melky Runtukahu; Dudik Djaja Sidarta; Vieta Imelda Cornelis (Rechtsvinding, 2026)
The development of information technology and the increasingly massive use of the internet have increased the risk of criminal acts of misuse of personal data, especially through cybercrime modes such as phishing and online fraud. The misuse of personal data not only causes material harm to the victim, but also threatens the right to privacy as part of human rights. This article aims to analyze criminal law enforcement against perpetrators of the crime of misusing personal data through the internet and identify the factors that affect the effectiveness of law enforcement. This research uses normative legal research methods with legislative and conceptual approaches. The legal materials used include laws and regulations, especially the Law on Information and Electronic Transactions and Law Number 27 of 2022 concerning Personal Data Protection, supported by relevant scientific literature and journals. The results of the study show that although the legal framework related to personal data protection has been strengthened, law enforcement against the crime of misuse of personal data through the internet still faces various obstacles, including limited capabilities of law enforcement officials, inadequate technological facilities, and low public legal awareness. Therefore, it is necessary to strengthen the capacity of law enforcement officials, optimize information technology facilities, and increase people's digital literacy to realize effective and fair personal data protection.